Comorbid psoriasis in systemic lupus erythematosus: a cohort study from a tertiary referral centre and the National Patient Register in Sweden - Christopher Sjöwall; Ioannis Parodis; Elizabeth Arkema; Tomas Walhelm; Charlotta Enerbäck (Lupus Science and Medicine)
Objectives To investigate the prevalence of psoriasis in SLE using a Swedish regional cohort and a nationwide cohort from the National Patient Register (NPR). Furthermore, we compared clinical features between patients with and without comorbid psoriasis.Methods In total, 351 patients diagnosed with SLE based on the 1982 American College of Rheumatology and/or the 2012 Systemic Lupus International Collaborating Clinics criteria from Linköping University Hospital were evaluated. We obtained patient-reported and relevant clinical data extracted in 2024. Individuals with coexisting psoriasis were identified via the International Classification of Diseases code L40 and subsequent confirmation through chart review in the regional cohort. In the NPR, 7490 subjects with SLE living in Sweden in 2022 were identified, as well as therapies obtained from the Prescribed Drug Register.Results We identified 12 subjects with SLE and coexisting psoriasis (3.4%) in the regional cohort and 367 patients (4.9%) in the nationwide cohort. Men were proportionally more common in the group with comorbid psoriasis in both cohorts. Patients with psoriasis reported more pain on a visual analogue scale (median 45.5/100 mm, IQR 23.3–58.3) compared with those without coexisting psoriasis (median 27.0/100 mm, IQR 7.0–50.5, p<0.04). We observed no differences in damage accrual or clinical phenotypes between the two groups. Subjects with psoriasis were more frequently prescribed methotrexate in the nationwide cohort.Conclusion The prevalence of coexisting psoriasis in patients with SLE in Sweden was estimated to be 3.4–4.9%. Individuals with comorbid psoriasis reported more pain and were more likely to be prescribed methotrexate than those without psoriasis.